A Comparative Study on Inhibition of Breast Cancer Cells and Tumors in Mice by Carotenoid Extract and Nanoemulsion Prepared from Sweet Potato (Ipomoea batatas L.) Peel - Hsin-Yen Hsu; Bing-Huei Chen (MDPI AG, 2022)
The objectives of this study were to determine carotenoid composition in sweet potato (TNG66) peel and prepare carotenoid nanoemulsion to study its inhibition effect on breast cancer cells MCF-7 and tumors in mice. Results showed that a total of 10 carotenoids were separated within 30 min by employing a YMC C30 column and a gradient mobile phase of methanol/acetonitrile/water (74:14:12, v/v/v) and dichloromethane (B) with a flow rate of 1 mL/min, column temperature of 25 °C, and detection wavelength of 450 nm. Following quantitation, all-trans-β-carotene was present in the highest amount (663.8 μg/g). The method validation data demonstrated a high accuracy and precision of this method. The carotenoid nanoemulsion was prepared by mixing an appropriate proportion of carotenoid extract, Tween 80, PEG 400, soybean oil and deionized water with the mean particle size being 15.7 nm (transmission electron microscope (TEM)), polydispersity index 0.238, encapsulation efficiency 97% and zeta potential −69.8 mV. A high stability of carotenoid nanoemulsion was shown over a 90-day storage period at 25 °C and during heating at 100 °C for 2 h. The release percentage of total carotenoids from carotenoid nanoemulsion under gastric and intestinal condition was 18.3% and 49.1%, respectively. An antiproliferation study revealed that carotenoid nanoemulsion was more effective than carotenoid extract in inhibiting the growth of human breast cancer cells MCF-7. Following treatments of paclitaxel (10 μg/mL), carotenoid nanoemulsion (20 and 10 μg/mL) and carotenoid extract (20 and 10 μg/mL), the tumor weight of mice respectively decreased by 77.4, 56.2, 40.3, 36.1 and 18.7%, as well as tumor volume of mice by 75.4, 65.0, 49.7, 46.7 and 26.5%. Also, both carotenoid extract and nanoemulsion could reduce the levels of epidermal growth factor (EGF) and (vascular endothelial growth factor (VEGF) in serum, with the latter being more effective. This finding suggested that carotenoid nanoemulsion was more effective than carotenoid extract in inhibiting tumor growth in mice.